An integrated global chemomics and system biology approach to analyze the mechanisms of the traditional Chinese medicinal preparation Eriobotrya japonica – Fritillaria usuriensis dropping pills for pulmonary diseases. Issue 1 (December 2015) - Tao, Jin; Hou, Yuanyuan; Ma, Xiaoyao; Liu, Dan; Tong, Yongling; Zhou, Hong; Gao, Jie; Bai, Gang
Abstract Background Traditional Chinese medicine (TCM) herbal formulae provide valuable therapeutic strategies. However, the active ingredients and mechanisms of action remain unclear for most of these formulae. Therefore, the identification of complex mechanisms is a major challenge in TCM research. Methods This study used a network pharmacology approach to clarify the anti-inflammatory and cough suppressing mechanisms of the Chinese medicinal preparationEriobotrya japonica – Fritillaria usuriensis dropping pills (ChuanbeiPipa dropping pills, CBPP). The chemical constituents of CBPP were identified by high-quality ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF-MS), and anti-inflammatory ingredients were selected and analyzed using the PharmMapper and Kyoto Encyclopedia of Genes and Genomes (KEGG) bioinformatics websites to predict the target proteins and related pathways, respectively. Then, an RNA-sequencing (RNA-Seq) analysis was carried out to investigate the different expression of genes in the lung tissue of rats with chronic bronchitis. Results Six main constituents affected 19 predicted pathways, including ursolic acid and oleanolic acid fromEriobotrya japonica  (Thunb.) Lindl. (Eri ), peiminine fromFritillaria usuriensis  Maxim. (Fri ), platycodigenin and polygalacic acid fromPlatycodon grandiflorum (Jacq.) A. DC. (Pla ) and guanosine fromPinellia ternata (Thunb.) Makino. (Pin ). Expression of 34 genes was significantly decreased after CBPP treatment, affecting four therapeutic functions: immunoregulation, anti-inflammation, collagen formation and muscle contraction. Conclusion The active components acted on the mitogen activated protein kinase (MAPK) pathway, transforming growth factor (TGF)-beta pathway, focal adhesion, tight junctions and the action cytoskeleton to exert anti-inflammatory effects, resolve phlegm, and relieve cough. This novel approach of global chemomics-integrated systems biology represents an effective and accurate strategy for the study of TCM with multiple components and multiple target mechanisms.